Mapping Markush - Stefan Wagner; Christian Sternitzke; Sascha G. Walter (European School of Management and Technology (ESMT), 2022)
Markush structures are molecular skeletons containing not only specific atoms but also placeholders to represent broad sets of chemical (sub)structures. As genus claims, they allow a vast number of compounds to be claimed in a patent application without having to specify every single chemical entity. While Markush structures raise important questions regarding the functioning of the patent system, innovation researchers have been surprisingly silent on the topic. This paper summarizes the ongoing policy debate about Markush structures and provides first empirical insights into how Markush structures are used in patent documents in the pharmaceutical industry and how they affect important outcomes in the patent prosecution process. While not causing frictions in the patent prosecution process, patent documents containing Markush structures have an increased likelihood to restrict the patentability of followon inventions and to facilitate the construction of broad patent fences.
urn:nbn:de:101:1-2022071511181773147338
Keywords: 650; Pharmaceutical industry; innovation; patents; Markush structures